Modulating the experience of agency: a positron emission tomography study - Farrer, C; Franck, N; Georgieff, N; Frith, C.D; Decety, J; Jeannerod, M (NeuroImage (Orlando, Fla.), 2003)
This study investigated agency, the feeling of being causally involved in an action. This is the feeling that leads us to attribute an action to ourselves rather than to another person. We were interested in the effects of experimentally modulating this experience on brain areas known to be involved in action recognition and self-recognition. We used a device that allowed us to modify the subject’s degree of control of the movements of a virtual hand presented on a screen. Four main conditions were used: (1) a condition where the subject had a full control of the movements of the virtual hand, (2) a condition where the movements of the virtual hand appeared rotated by 25° with respect to the movements made by the subject, (3) a condition where the movements of the virtual hand appeared rotated by 50°, and (4) a condition where the movements of the virtual hand were produced by another person and did not correspond to the subject’s movements. The activity of two main brain areas appeared to be modulated by the degree of discrepancy between the movement executed and the movement seen on the screen. In the inferior part of the parietal lobe, specifically on the right side, the less the subject felt in control of the movements of the virtual hand, the higher the level of activation. A reverse covariation was observed in the insula. These results demonstrate that the level of activity of specific brain areas maps onto the experience of causing or controlling an action. The implication of these results for understanding pathological conditions is discussed.